A Medicine with Alkaloids New Information about the Biology and Importance of Plants - Rashidov Negmurod Elmurodovich; Radjabov Saloxiddin Toirtoshevich (Researchparks Publishing, 2022)
The demand for medicinal plants is growing. Therefore, the study of medicinal plants, the study of their effects on diseases, the preparation of medicines from them is one of the most important topics. This article provides the latest information on the cultivation of medicinal plants, the impact of medicinal plants on diseases and the preparation of medicines from them in medicine.